Handbook of social capital the troika of sociology, political science, and economics - Svendsen, Gert Tinggaard 1963-; Svendsen, Gunnar Lind Haase 1965- (Edward Elgar, 2009)
A guide to the study of bonding and bridging social capital networks. It intends to serve as a bridge for students and scholars within the various social sciences. It explores the different scientific approaches that are needed if international research is to embrace both the bright and the more shadowy aspects of social capital.